A study of DNA/BSA interaction and catalytic potential of oxidovanadium(v) complexes with ONO donor ligands. Issue 45 (2nd November 2016) - Dash, Subhashree P.; Panda, Alok K.; Dhaka, Sarita; Pasayat, Sagarika; Biswas, Ashis; Maurya, Mannar R.; Majhi, Paresh Kumar; Crochet, Aurélien; Dinda, Rupam
Abstract : The study of DNA/BSA interaction and the catalytic potential of five mono- and dinuclear oxidoethoxido vanadium(v ) complexes. Abstract : The study of DNA/BSA interaction and the catalytic potential of four mononuclear oxidoalkoxido vanadium(v ) [V V O(L 1–4 )OEt] (1–4 ) and one dinuclear oxidoalkoxido mixed-ligand vanadium(v ) [{VO(L 2 )OEt}2 (Q)]{Q = 4, 4′-bipyridine}(5 ) complexes, with tridentate binegative aroylazine ligands are reported [where H2 L 1 = anthranylhydrazone of 2-hydroxy-1-napthaldehyde, H2 L 2 = salicylhydrazone of 2-hydroxy-1-napthaldehyde, H2 L 3 = benzoylhydrazone of 2-hydroxy-1-acetonaphthone, H2 L 4 = anthranylhydrazone of 2-hydroxy-1-acetonaphthone]. All the complexes are characterized by elemental analysis as well as various spectroscopic techniques. Single crystal X-ray diffraction crystallography of2 reveals that the metal centre is in distorted square pyramidal geometry with O4 N coordination spheres, whereas5 exhibits a distorted octahedral geometry around the metal center. In addition, all the complexes (1–5 ) show moderate DNA binding propensity which is investigated using UV-vis absorption titration, circular dichroism, thermal denaturation and fluorescence spectral studies. The experimental results show that the complexes effectively interact with CT-DNA through both minor and major groove binding modes, with binding constants ranging from 10 4 −10 5 M −1 . Among1–5, complexes3 and4 show higher binding affinity towards CT-DNA than others and at the same time also exhibit negative Δ T m values of about ∼1.5 and 1.0 °C which resembles the properties shown by cisplatin. All complexes show moderate photo-induced cleavage of pUC19 supercoiled plasmid DNA with complex3 showing the highest photo induced DNA cleavage activity of ∼48%. In coherence with the DNA interaction studies, 3 and4 also exhibit good binding affinity towards BSA in the range of 10 10 −10 11 M −1, which is also supported by their ability to quench the tryptophan fluorescence emission spectra of BSA. All the complexes show remarkable photo-induced BSA cleavage activity (>90%) at a complex concentration of 50 μM. The catalytic potential of1–5 is also tested for the oxidative bromination of styrene, salicylaldehyde and oxidation of methyl phenyl sulphide. All the reactions show a high percentage of conversion (>90%) with a high turnover frequency (TOF). Particularly, in the oxidative bromination of styrene the percentage of conversion and TOF vary from 96–98% and 8000–19 600 (h −1 ) respectively, which signifies the potential of these oxidovanadium(v ) complexes to stimulate research for the synthesis of a better catalyst.